ANAK JALANAN DI KAMPUNG MISKIN PERKOTAAN Studi Kasus Penanganan Anak Jalanan di Pedongkelan Jakarta Timur - Hari Harjanto Setiawan (Politeknik Kesejahteraan Sosial, 2007)
The Community development programs are preventive in aproach. This approach offersan alternative to institutionalization of street children. It is an atempt address the problem where it stars family and community of the child. The Community development process on the families of street children and others urban poor children and their community to enable them to make those change within themselves that will lead to change in opportunities for their children to keep them of the streets. It has several main components: advocacy, community organization, livelihood development and educational assistance including value clarification and skills trainimg. Family in the Kampung Pedongkelan have high risk, because they unable to fulfill need of his life and perforced to employ its child as street musician, sale of newspaper, worker of park and sale of water. This children in general, still live with family. This street children is categorized as children at high risk, so that choose model in handling is with model of Community development that is one of the model handling of street children applying strategy to return to family and prevent children become street children. Handling bases aimed at reinforcement of family function, income generating and utilization of potency had by community. Goal of Community development is to improve ability of family as society member in protecting, mothering and fulfilling of children right.Key words : Street Children, Community Development.